Investigate the reduction of mill scale with low grade coal through solid gas reactor. (2021) - Shekhawat, Deepika; Gautam, Nishant; Banerjee, M.K.; Patnaik, Amar
Abstract: Over the past few decades, consistent efforts have been made by numerous steel and ironmaking industries in the direction of reutilizing the "by-product" of rolling mill i.e. the mill scale in wake of ever rising cost of superior quality lump ores and its unavailability. Also, utilization of low-grade coal composing higher content of volatile matter has constantly been another concern for the researchers. Rajasthan has a vast reserve of low-grade coal. The objective of the study undertaken is to utilize both of the aforestated raw materials (of Indian origin) in a solid gas reactor. It is devoted to assess and study the reduction of mill scale in the presence of single gaseous reductant (i.e. CO gas). The optimal process parameters (i.e. reduction temperature, mill scale size, reduction time and mill scale to coal ratio) were also analysed during the reduction. Current study investigates the impact of mill scale size (300 to 825 µm), reduction temperature (800 to 1100 °C in steps of 100 °C), reduction time (60–240 min), and mill scale to coal ratio (1:1, 1:2, 1:3 and 1:4) on accomplishable Fe (metallic iron) percentage and its metallization. Lower mill scale size (300 µm) particles, higher reduction temperature (1100 °C), higher reduction time (240 mins), and mill scale to coal ratio (1:3) yielded higher percentage of metallic iron content (76.28%) and metallization (96.75%). During the entire study the flow rate of CO is maintained at 4.5 LPM (litres per minute). The chemical analysis of mill scale is carried out using X-ray fluorescence (XRF), and mill scale particle size and dispersion of mill scale is analysed by scanning electron microscope (SEM). The presence of bright and dark phases in the FE-SEM micrographs confirm the presence of metallic and not metallic elements. It became apparent that reduction of mill scale using low-grade coal presents the most promising results with the solid gas reactor yielding a greater degree of metallization as compared to the rotary kiln and RI-RDI furnaces.